Running away from the jab: factors associated with COVID-19 vaccine hesitancy in Brazil - Paschoalotto, Marco Antonio Catussi; Costa, Eduardo Polena Pacheco Araújo; Almeida, Sara Valente de; Cima, Joana; Costa, Joana Gomes da; Santos, João Vasco; Barros, Pedro Pita; Passador, Claudia Souza; Passador, João Luiz (Revista de Saúde Pública, 2021)
OBJECTIVE: To investigate how sociodemographic conditions, political factors, organizational confidence, and non-pharmaceutical interventions compliance affect the COVID-19 vaccine hesitancy in Brazil. METHODS: Data collection took place between November 25th, 2020 and January 11th, 2021 using a nationwide online survey. Subsequently, the researches performed a descriptive analysis on the main variables and used logistic regression models to investigate the factors associated with COVID-19 vaccine hesitancy. RESULTS: Less concern over vaccine side effects could improve the willingness to be vaccinated (probability changed by 7.7 pp; p < 0.10). The current vaccine distrust espoused by the Brazilian president is associated with vaccine hesitancy, among his voter base. Lower performance perception (“Very Bad” with 10.7 pp; p < 0.01) or higher political opposition (left-oriented) regarding the current presidency is associated with the willingness to be vaccinated. Higher compliance with non-pharmaceutical interventions (NPIs) is usually positively associated with the willingness to take the COVID-19 vaccine (+1 score to NPI compliance index is associated with higher willingness to be vaccinated by 1.4 pp, p < 0.05). CONCLUSION: Willingness to be vaccinated is strongly associated with political leaning, perceived federal government performance, vaccine side effects, and compliance with non-pharmaceutical interventions (NPIs).